Incidence and Risk Factors of Non-Alcoholic Fatty Liver Disease among Non-Obese Patients Attending at Department of Gastroenterology, BSMMU - Biswas, Prodip Kumar; Kabir, AKM Humayon; Karim, Mohammad Enamul; Hossain, Mohammed Shahadat; Vhadury, Suvash Chandra; Rhaman, Mir Masudur; Masud, Hasan; Khan, Masudur Rahman (Journal of Medicine, 2015)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is a distinct clinicopathologic entity characterized histologically by a spectrum ranging from simple steatosis to steatohepatitis (NASH), cirrhosis and even hepatocellular carcinoma (HCC). Objective: To determine the incidenceand identify the risk factors of NAFLD in non-obese patients. Methods: It was a cross sectional study done in Department of gastroenterology, Nuclear Medicine and ultrasound, Radiology and Imaging, Virology, Biochemistry, BSMMU, Dhaka from March 2012 to June 2014. The patients more or equal to 18 years, non-obese were included. In this study total 190 patients were enrolled. Results: Among them 38 patients were with fatty liver and 152 patients without fatty liver on the basis of ultrasonogram. Where 141 were male and 49 were female with mean age was 49.24 + 9.05 years. Among total, 18.9% had diabetes mellitus, 28.4% had dislipidaemia 24.4% had history of hypertension. Total 18.9% patients having history of diabetes mellitus, normal vs fatty liver disease (20% vs 42.1%, p <0.001) and history of dyslipidemia (10.5% vs 100% , p <0.001), Haemoglobin percentage was 12.16 + 1.32 gm/dL, urine routine microscopic examination glucose present in 9.5% patients. SGPT 56.34 + 16.09 IU/L, SGOT 41.62 + 5.94 IU/L, alkaline phosphatase 99.31+ 19.76 IU/L. We found 6.3% patients were HBsAg positive and no patient was Anti HCV positive. Conclusion: Sedentary life style, Metabolic syndrome, DM, dyslipidameia, are risk factors of NAFLD in non obese person. Elevated liver enzymes are consequences of NAFLD. Though this study has some limitations, it will give some information about emerging liver disease without viral hepatitis. J MEDICINE July 2015; 16 (2) : 89-92